ANALISIS PERBAIKAN PROSES PRODUKSI PADA UKM TAHU RONGGOLAWE - Novia septrianis; Arsyad Sumantika (Computer Science and Industrial Engineering, 2026)
Small and Medium Enterprises (SMEs) play a strategic role in the national economy, especially in the food sector such as tofu production. Many food SMEs still face quality issues due to unstandardized production processes, limited sanitation, and weak quality control. This study analyzes and proposes improvements for the tofu production process at UKM Tahu Ronggolawe, Batam City, to enhance product quality and efficiency. Methods include Six Sigma, Good Manufacturing Practices (GMP), and Work Improvement in Small Enterprises (WISE). Data were collected through observation, interviews, and documentation of production and defect data from January to June 2025. Six Sigma analysis shows an average DPMO of 37,864 and an average sigma level of 3.28, indicating moderate process capability with notable defect opportunities. GMP evaluation reveals sanitation, worker hygiene, equipment, production environment, and documentation mostly fall into less compliant or non-compliant categories. WISE assessment indicates work systems, production layout, machine safety, welfare facilities, and organization are poorly structured and lack written SOPs. Proposed improvements include sanitation SOPs, routine employee work rules, better hygiene practices, and gradual optimization of production layout and environment. Integrating Six Sigma, GMP, and WISE is expected to reduce defects, improve product consistency, and achieve a more efficient, hygienic, and sustainable tofu production process.